Harbans Lal Chhibber : A Bibliography - Alam, Sarfaraz (National Geographical Journal of India, 2022)
This article maps the academic trails of late Prof. Harbans Lal Chhibber (1899-1955) with the help of bibliography of his published and unpublished works. Prof. Chhibber was one of the foremost earth scientists of India. During the course of over three decades of academic career (1923-1955), he made seminal contributions in various sub-fields of geography, geology, geophysics and ceramics. Only an exceptional scholar like him could contribute in such diverse fields of knowledge. However, his writings are scattered in various books, journals, bulletins and proceedings of seminars and conferences published from across the world. Therefore, an exhaustive list of his research contributions is lacking. Though his bio-data, available with the Indian National Science Academy (New Delhi), provides a reasonably extensive list of his published works, it is by no means a complete one. Some of his works published prior to 1952 are not given in this bio-data. Further, he published many papers and articles during the last three years of his life. In view of this, the present article provides a comprehensive bibliography of the research works of Harbans Lal Chhibber. It would benefit students and researchers interested in his academic life and works